Using contemporary behavior change science to design and implement an effective nutritional intervention within professional Rugby League - Costello, N.; McKenna, J.; Sutton, L.; Deighton, K.; Jones, B. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Designing and implementing successful dietary intervention is integral to the role of sport nutrition professionals as they attempt to positively change the dietary behavior of athletes. High-performance sport is a time-pressured environment where immediate results can often supersede pursuit of the most effective evidence-based practice. However, efficacious dietary intervention necessitates comprehensive, systematic, and theoretical behavioral design and implementation, if the habitual dietary behaviors of athletes are to be positively changed. Therefore, this case study demonstrates how the Behaviour Change Wheel was used to design and implement an effective nutritional intervention within a professional rugby league. The eight-step intervention targeted athlete consumption of a high-quality dietary intake of 25.1 MJ each day to achieve an overall body mass increase of 5 kg across a 12-week intervention period. The capability, opportunity, motivation, and behavior model and affordability, practicability, effectiveness/cost-effectiveness, acceptability, safety, and equity criteria were used to identify population-specific intervention functions, policy categories, behavior change techniques, and modes of intervention delivery. The resulting intervention was successful, increasing the average daily energy intake of the athlete to 24.5 MJ, which corresponded in a 6.2 kg body mass gain. Despite consuming 0.6 MJ less per day than targeted, secondary outcome measures of diet quality, strength, body composition, and immune function all substantially improved, supporting sufficient energy intake and the overall efficacy of a behavioral approach. Ultimately, the Behaviour Change Wheel provides sport nutrition professionals with an effective and practical stepwise method to design and implement effective nutritional interventions for use within high-performance sport.